Being in a Romantic Relationship Is Associated with Reduced Gray Matter Density in Striatum and Increased Subjective Happiness - Kawamichi, Hiroaki; Sugawara, Sho K.; Hamano, Yuki H.; Makita, Kai; Matsunaga, Masahiro; Tanabe, Hiroki C.; Ogino, Yuichi; Saito, Shigeru; Sadato, Norihiro (Frontiers in Psychology, 2016)
Romantic relationship, a widespread feature of human society, is one of the most influential factors in daily life. Although stimuli related to romantic love or being in a romantic relationship commonly result in enhancement of activation or functional connectivity of the reward system, including the striatum, the structure underlying romantic relationship-related regions remain unclear. Because individual experiences can alter gray matter within the adult human brain, we hypothesized that romantic relationship is associated with structural differences in the striatum related to the positive subjective experience of being in a romantic relationship. Because intimate romantic relationships contribute to perceived subjective happiness, this subjective enhancement of happiness might be accompanied by the experience of positive events related to being in a romantic relationship. To test this hypothesis and elucidate the structure involved, we compared subjective happiness, an indirect measure of the existence of positive experiences caused by being in a romantic relationship, of participants with or without romantic partners (N = 68). Furthermore, we also conducted a voxel-based morphometry (VBM) study of the effects of being in a romantic relationship (N = 113). Being in a romantic relationship was associated with greater subjective happiness and reduced gray matter density within the right dorsal striatum. These results suggest that being in a romantic relationship enhances perceived subjective happiness via positive experiences. Furthermore, the observed reduction in gray matter density in the right dorsal striatum may reflect an increase in saliency of social reward within a romantic relationship. Thus, being in a romantic relationship is associated with positive experiences and a reduction of gray matter density in the right dorsal striatum, representing a modulation of social reward.